(untitled) (Perner’s Contacts, 2013)
The aim of the paper is short description of possibilities of data dependent systems (DDS) mathematical apparatus using. Basic form of DDS expression is form a stochastic time series of process which can be used to description and modelling of stochastic process, e.g. operational process. The paper contains a briefly characteristics of fundamental terms and equations of time series theory mathematical apparatus, algorithm of a statistically adequate discrete model of stochastically dynamic system and developed strategy application on real process.